Regioquímica da reação de alquilação entre 4- (trialometil)pirimidin-2(1h)-onas e 5-bromoenonas - Mittersteiner, Mateus (2022)
The present thesis reports the reactivity study between 5-bromo-1,1,1,-trifluoro-4- methoxy(amino)pent-3-en-2-ones (5-bromoenones/enaminones) towards 5- or 6- substituted 4-(trihalomethyl)pyrimidin-2(1H)-ones. During the initial tests, it was found that the chemoselectivity of the reaction (selective towards N- or O-alkylation) is highly influenced by the presence or absence of a substituent at the 6- position of the starting pyrimidin-2(1H)-one. In this manner, 10 N-alkylated and 25 O-alkylated products were prepared as sole compounds, with full selectivity, in 60 – 94% yields. In a second moment, the β-enaminone moiety present in the alkylated products was cyclocondensed with NO-, NN- e NCN-dinucleophiles, with the aim of obtaining conjugated isoxazoles, pyrazoles and pyrimidines. In this sense, 4 N-azolylmethyl-pyrimidin-2(1H)-2-ones and 6- O-azolylmethyl-pyrimidines were obtained through cyclocondensation reactions of type [3+2] in satisfactory yields. When 2-methylisothiourea sulfate was used to perform the [3+3] cyclocondensation reaction, yields of 8 – 10% were observed. As to overcome this, a convergent synthetic strategy was used, by preparing, isolated, 4-(halomethyl)-2- (methylsulfanyl)-6-(trihalomethyl)pyrimidines through the cyclocondensation between 5-bromo-1,1,1-trifluoro(chloro)-4-methoxypent-3-en-2-ones and 2-methylisothiourea sulfate, which are obtained in 59 – 85% yields. These halomethyl pyrimidines are used as electrophiles that insert the pyrimidine nucleus as heterocyclic block previously prepared. The selectivity of the reaction was maintained the same as in the first synthetic step of this study, and, when reacted with 4-(trifluoromethyl)pyrimidin-2(1H)-ones, only the O-alkylation products were obtained in the presence of a substituent at the 6-position. In this step, the electrophile used in the alkylation reaction was also evaluated, thus (4- chloro/bromo/iodomethyl)pyrimidines were prepared and the 4-(iodomethyl)-2- (methylsulfanyl)-6-(trihalomethyl)pyrimidines were found to be the ones that react faster and more efficient for this reaction type. In this manner, 18 O-alkylated derivatives were prepared in yields 70 – 98%. In the absence of a substituent at the 6-position, the expected N-alkylated products could not be obtained through any of the proposed methodologies. Keywords: Pyrimidinones, enones, heterocycles, alkylation, selective reaction.